Enhancing Hydroponic Farming with IoT: Empowering Innovative and Speculative Young Farmers - Salam, Anis Fuad; AM, Kartina; Mirajiani, Mirajiani (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
The integration of Internet of Things (IoT) technology into hydroponic farming systems presents a transformative opportunity to modernize agriculture and attract the younger generation to the sector. This study explores the effectiveness of IoT applications in hydroponic cultivation to foster a new wave of tech-savvy, innovative young farmers. Hydroponics, a soil-less farming method that utilizes nutrient-rich water, offers various advantages such as efficient water use, controlled environments, and suitability for limited land spaces. When combined with IoT—through the use of sensors, automation, and real-time monitoring—hydroponic systems become more efficient, sustainable, and appealing to youth interested in modern agriculture. The research outlines the types of hydroponic systems and their integration with IoT, highlights the benefits and challenges of such implementation, and emphasizes the pivotal role of government in supporting young farmers through education, infrastructure, financing, and policy. Key challenges identified include high initial costs, limited internet infrastructure, and lack of technological literacy among farmers. Despite these barriers, the adoption of IoT has the potential to increase productivity, reduce manual labor, and elevate the status of farming as a profitable and high-tech career path for young people. The study concludes that a strong collaboration between government, educational institutions, and the private sector is crucial to empower the next generation of innovative farmers and ensure the sustainability of the agricultural sector.